2010
DOI: 10.1590/s0036-46652010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Human toxocariasis: a seroepidemiological survey in the Amazonian city of Yurimaguas, Peru

Abstract: SUMMARYThe aim of this study was to determine the seroprevalence of the infection by Toxocara in the general population of the Amazonian city of Yurimaguas, Peru. From March to August 2008, a total of 300 subjects were sampled and tested by means of a Toxocara ELISA-IgG test. A clinical and epidemiological questionnaire was used to assess the symptomatology and risk factors associated with human toxocariasis. The overall rate of seropositivity was 35.66%, with a significant high proportion in children (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 33 publications
5
35
2
3
Order By: Relevance
“…For instance, while some researchers have verified either an increase of the toxocariasis prevalence in the male population [20,21] , others have shown that females are more closely associated with the zoonosis [8] . No association between gender and an ELISA positive result for toxocariasis has also been observed [22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, while some researchers have verified either an increase of the toxocariasis prevalence in the male population [20,21] , others have shown that females are more closely associated with the zoonosis [8] . No association between gender and an ELISA positive result for toxocariasis has also been observed [22] .…”
Section: Discussionmentioning
confidence: 99%
“…However, having a pet was not considered a risk/protective factor for toxocariasis. Keeping a dog in a household has been recognised as a risk factor in some [31,32] but not all surveys [21,33] . The influence of cat ownership on a positive ELISA test has been less studied.…”
Section: Discussionmentioning
confidence: 99%
“…These findings correlate with the known risk factors for Toxocara infection such as: contact with contaminated soil, low socioeconomic conditions and poor hygienic habits. In descending order, the most frequent symptoms were: respiratory signs (77.96 %), ocular signs (61.02 %), hepatic compromise (38.98 %), abdominal pain (30.51 %) and cutaneous signs (27.12 %) [2].…”
Section: Toxocariasis In Perumentioning
confidence: 99%
“…These nematodes develop the adult stage in the intestines of cats and dogs, where each female produces 200 000 eggs per day. These eggs are eliminated from the body and become infecting after [2][3][4][5] weeks. After being ingested by humans, the larvae go through the intestinal wall, migrating via the veins into the liver and the rest of the body, where they remain as larvae [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the subjects with positive serology, ocular signs or symptoms ranged from 17.74% to 36.45% [3,4].…”
Section: Introductionmentioning
confidence: 99%